Comparison of efficacy and safety of combined phacoemulsification, goniosynechialysis and goniotomy with trabeculectomy in advanced primary angle-closure glaucoma: a retrospective observational study - Zhang, Wenzhe; Wang, Pengyun; Wang, Chen; Liu, Wenhui; Wu, Jiayin; Shen, Lin; Kurmi, Rachita; Guo, Hui (Frontiers in Medicine, 2025)
PurposeThe study is a retrospective observational study. This study aimed to compare the intraocular pressure (IOP) lowering effect of phacoemulsification combined with intraocular lens implantation (PEI), Goniosynechialysis (GSL), and goniotomy (GT) vs. trabeculectomy (TRAB) in eyes with medically uncontrolled advanced primary angle-closure glaucoma (PACG) at a 12-month follow-up.MethodsPatients with medically uncontrolled advanced PACG with 360° peripheral anterior synechia (PAS) were included in this study. The patients were divided into two groups based on the surgical technique: PEI + GSL + GT and TRAB. Each patient completed a 12-month postoperative follow-up.ResultsA total of 73 eyes from 71 patients were included in this study, 43 eyes of which received PEI + GSL + GT and 30 eyes of which received TRAB. At 12 months follow-up, the mean preoperative and postoperative IOP was 27.63 ± 11.38 and 16.46 ± 4.04 mmHg in the PEI + GSL + GT group (P < 0.001), and 32.83 ± 13.91 and 15.21 ± 2.58 mmHg in the TRAB group (P < 0.001), respectively. As for success rates, among the 43 eyes in the PEI + GSL + GT group, 35 eyes (81.40%) and 40 eyes (93.02%) achieved complete and qualified success with IOP ≤21 mmHg. In the TRAB group, out of 30 eyes, 25 eyes (83.33%) and 29 eyes (96.67%) achieved complete and qualified success with IOP ≤21 mmHg, respectively. Among the 43 eyes in the PEI + GSL + GT group, 33 eyes (76.74%) and 37 eyes (86.05%) achieved complete and satisfactory success with IOP ≤18 mmHg, respectively. While in the TRAB group, 24 eyes (80.00%) and 27 eyes (90.00%) achieved complete and qualified success, respectively, with IOP ≤18 mmHg. There was no significant difference in visual field (VF) between preoperative and postoperative periods in both groups. All eyes exhibited no serious postoperative complications that threatened vision.ConclusionsPEI + GSL + GT and TRAB demonstrated comparable efficacy in lowering IOP, reducing medications, and preserving VF in medically uncontrolled advanced PACG. Moreover, PEI + GSL + GT exhibited fewer complications, avoid bleb-related complications and may be a novel minimally invasive alternative for treating advanced PACG.